Corrosion mitigation in desalination plants by ammonium-based ionic liquid - M. A. Deyab (Nature Portfolio, 2021)
Abstract CuNi (90:10) alloy is widely used in desalination plants. CuNi alloy corrosion in sulfide-containing seawater is the fundamental problem in the desalination industry. Here we have confronted this difficulty by using ammonium-based ionic liquid (Diethyl (2-methoxyethyl)-methyl ammonium Bis(fluorosulfonyl)imide) [DEMEMA][FSI]. The results revealed that the [DEMEMA][FSI] can suppress Cu–Ni alloy corrosion in a solution of (3.5% NaCl + 10 ppm sulphide) with an efficiency of 98.4% at 120 ppm. This has been estimated by electrochemistry and gravimetry. Furthermore, [DEMEMA][FSI] inhibits the growth of sulfate-reducing bacteria SRB in saline water. Surface morphology testing confirmed [DEMEMA][FSI] adsorption on Cu–Ni surface alloys. In addition, quantum calculations have been used to theoretically predict inhibition efficiency [DEMEMA][FSI].